THE RETINAL TARGETS OF CENTRIFUGAL NEURONS AND THE RETINAL NEURONS PROJECTING TO THE ACCESSORY OPTIC-SYSTEM - Nickla, D. L.; Gottlieb, M. D.; Marin, G.; ROJAS, X; Britto, LRG; Wallman, J. (Cambridge Univ Press, 1994)
In birds, neurons of the isthmo-optic nucleus (ION), as well as ''ectopic'' neurons, send axons to the retina, where they synapse on cells in the inner nuclear layer (INL). Previous work has shown that centrifugal axons can be divided into two anatomically distinct types depending on their mode of termination: either ''convergent'' or ''divergent'' (Ramon y Cajal, 1889; Maturana and Frenk, 1965). We show that cytochrome-oxidase histochemistry specifically labels ''convergent'' centrifugal axons and target neurons which appear to be amacrine cells, as well as three ''types'' of ganglion cells: two types found in the INL (displaced ganglion cells) and one in the ganglion cell layer. Labeled target amacrine cells have distinct darkly labeled ''nests'' of boutons enveloping the somas, are associated with labeled centrifugal fibers, and are confined to central retina. Lesions of the isthmo-optic tract abolish the cytochrome-oxidase labeling in the centrifugal axons and in the target amacrine cells but not in the ganglion cells. Cytochromeoxidase-labeled ganglion cells in the INL are large; one type is oval and similar to the classical displaced ganglion cells of Dogiel, which have been reported to receive centrifugal input; the other type is rounder. Rhodamine beads injected into the accessory optic system results in retrograde label in both types of cells, showing that two distinct types of displaced ganglion cells project to the accessory optic system in chickens. The ganglion cells in the ganglion cell layer that label for cytochrome oxidase also project to the accessory optic system. These have proximal dendrites that ramify in the outer inner plexiform layer. Neither the target amacrine cells nor either of the displaced ganglion cells are immunoreactive for the inhibitory transmitter gamma aminobutyric acid. At least some of the target amacrine cells may, however, be cholinoceptive: we found that the antibody to the alpha-7 subunit of the nicotinic ACh receptor labels a population of cells in the INL that are similar in location, size, and the presence of labeled bouton-like structures to those we find labeled with cytochrome oxidase. This antibody also labels neurons in the ION proper but not ectopic cells. In conclusion, it appears that cytochrome oxidase may be a marker for ''convergent'' centrifugal axons and at least one of their target cells in the INL.
Keywords: AMACRINE CELL; CENTRIFUGAL FIBERS; CHICK; CYTOCHROME OXIDASE; DISPLACED GANGLION CELL; GABA; ISTHMO-OPTIC NUCLEUS; NICOTINIC ACETYLCHOLINE RECEPTOR